Evolution of a group of coronal holes associated with eruption of nearby prominences and CMEs - Gutiérrez Garro, Heidy (2014)
We present the results of detailed study of a set of activities developed on one of three enclosed sectors of solar region during the period of February 07-13, 2012. We found the sequence of certain topological perturbations of whole coronal holes (CHs) and their surroundings associated to the eruption of nearby prominence and subsequent Coronal Mass Ejections (CMEs). Especially, we observe the emergence of small bright points (BPs) and the formation of dimming regions (DRs) close to the filament's channel associated with a pre-evolution of filament/prominence eruption, whereas BPs disappearance and the shrinkage of CH we found associated with the post-eruption evolution of prominence and of CME.